BMP7 antagonizes proliferative vitreoretinopathy through retinal pigment epithelial fibrosis in vivo and in vitro. Issue 3 (1st November 2018) - Yao, Haipei; Ge, Tandi; Zhang, Yao; Li, Min; Yang, Shuai; Li, Hui; Wang, Fang
ABSTRACT: The major pathogenesis of proliferative vitreoretinopathy (PVR) is that retinal pigment epithelial (RPE) cells undergo epithelial‐mesenchymal transition (EMT) because of disordered growth factors, such as TGF‐β, in the vitreous humor. Bone morphogenetic proteins (BMPs) are pluripotent growth factors. In this study, we identified the antifibrotic activity of BMP7 in a PVR model both in vivo and in vitro . BMP7 expression was confirmed on the PVR proliferative membranes. BMP7 was down‐regulated in the PVR vitreous humor and TGF‐β–induced RPE cell EMT. In the in vivo studies, BMP7 injection attenuated PVR progression in the eyes of the rabbit model. Additionally, BMP7 treatment maintained RPE cell phenotypes and relieved TGF‐β2–induced EMT, migration, and gel contraction in vitro . BMP7 inhibited the TGF‐β2–induced up‐regulation of fibronectin and α–smooth muscle actin and the down‐regulation of E‐cadherin and zona occludens‐1 by balancing the TGF‐β2/Smad2/3 and BMP7/Smad1/5/9 pathways. These findings provide direct evidence of the ability of BMP7 in PVR inhibition and the potential of BMP7 for use in PVR therapeutic intervention.—Yao, H., Ge, T., Zhang, Y., Li, M., Yang, S., Li, H., Wang, F. BMP7 antagonizes proliferative vitreoretinopathy through retinal pigment epithelial fibrosis in vivo and in vitro . FASEB J. 33, 3212–3224 (2019). www.fasebj.org